Study of quantitative bacterial cultures of non-bronchoscopic samples in ventilator associated pneumonia - Azarudeen, Mohamed; Sharma, B. S.; Jain, Pankaj Kumar; Goyal, Alok Kumar; Malhotra, Bharti (International Journal of Contemporary Pediatrics, 2018)
Background: Diagnosis of VAP based on non bronchoscopic samples-ETA, NB-BAL culture. The aim is to study quantitative culture of the non-bronchoscopic sampling techniques such as Blind Broncho-alveolar lavage (NB-BAL) and endotracheal aspirates (ETA)in Ventilator Associated Pneumonia. It is a hospital based, observational study conducted in SPMCHI, Jaipur from September 2015 to September 2016. Methods: Seventy patients who were under mechanical ventilation for more than 48 hours and clinically suspected for VAP were included in the study and divided into early and late onset VAP. The NB-BAL and ETA were obtained from these patients and quantitative cultures were performed. Results: Out of the 70 samples analysed, 60 patients were found positive in BAL and 61 positive in ETA. The agreement between NB-BAL and ETA is 86.8%. GNBs remain the main burden of both early and late onset VAP. Most common organisms isolated were Enterobacter and Acinetobacter in early onset and Pseudomonas and Acinetobacter in late onset VAP. All the GNB isolates were sensitive to Polymyxin and Colistin and were resistant to majority of routinely used antibiotics. Conclusions: The quantitative culture of non-bronchoscopic samples is a useful alternative to bronchoscopy, in the diagnosis of VAP in resource deprived centers. MDR gram negative bacilli are the main causative agents of VAP.